Step
*
1
of Lemma
geo-colinear-implies
1. e : BasicGeometry-
2. BasicGeometryAxioms(e)
3. a : Point
4. b : Point
5. c : Point
6. ¬a # bc
7. ¬(((¬ab>ac) ∧ (¬bc>ac)) ∧ (¬a # bc))
8. ¬(((¬bc>ba) ∧ (¬ca>ba)) ∧ (¬b # ca))
9. ¬(((¬ca>cb) ∧ (¬ab>cb)) ∧ (¬c # ab))
10. ∀a,b,c,d:Point.  (ab>cd 
⇒ (¬cd>ab))
⊢ False
BY
{ ((Assert ¬¬((ab>ac ∨ bc>ac) ∨ a # bc) BY
          Auto)
   THEN (SupposeMore (-1) THEN Auto)
   THEN RepeatFor 2 ((D -1 THEN Auto))) }
1
1. e : BasicGeometry-
2. BasicGeometryAxioms(e)
3. a : Point
4. b : Point
5. c : Point
6. ¬a # bc
7. ¬(((¬ab>ac) ∧ (¬bc>ac)) ∧ (¬a # bc))
8. ¬(((¬bc>ba) ∧ (¬ca>ba)) ∧ (¬b # ca))
9. ¬(((¬ca>cb) ∧ (¬ab>cb)) ∧ (¬c # ab))
10. ∀a,b,c,d:Point.  (ab>cd 
⇒ (¬cd>ab))
11. ab>ac
⊢ False
2
1. e : BasicGeometry-
2. BasicGeometryAxioms(e)
3. a : Point
4. b : Point
5. c : Point
6. ¬a # bc
7. ¬(((¬ab>ac) ∧ (¬bc>ac)) ∧ (¬a # bc))
8. ¬(((¬bc>ba) ∧ (¬ca>ba)) ∧ (¬b # ca))
9. ¬(((¬ca>cb) ∧ (¬ab>cb)) ∧ (¬c # ab))
10. ∀a,b,c,d:Point.  (ab>cd 
⇒ (¬cd>ab))
11. bc>ac
⊢ False
Latex:
Latex:
1.  e  :  BasicGeometry-
2.  BasicGeometryAxioms(e)
3.  a  :  Point
4.  b  :  Point
5.  c  :  Point
6.  \mneg{}a  \#  bc
7.  \mneg{}(((\mneg{}ab>ac)  \mwedge{}  (\mneg{}bc>ac))  \mwedge{}  (\mneg{}a  \#  bc))
8.  \mneg{}(((\mneg{}bc>ba)  \mwedge{}  (\mneg{}ca>ba))  \mwedge{}  (\mneg{}b  \#  ca))
9.  \mneg{}(((\mneg{}ca>cb)  \mwedge{}  (\mneg{}ab>cb))  \mwedge{}  (\mneg{}c  \#  ab))
10.  \mforall{}a,b,c,d:Point.    (ab>cd  {}\mRightarrow{}  (\mneg{}cd>ab))
\mvdash{}  False
By
Latex:
((Assert  \mneg{}\mneg{}((ab>ac  \mvee{}  bc>ac)  \mvee{}  a  \#  bc)  BY
                Auto)
  THEN  (SupposeMore  (-1)  THEN  Auto)
  THEN  RepeatFor  2  ((D  -1  THEN  Auto)))
Home
Index